THU0388 The Associations between Age with The Clinical and Radiological Activity in Spondyloarthritis. (15th July 2016) - Li, P.H.; Ho, C.; Chung, H.Y.; Lau, C.S.
Abstract : Background: Spondyloarthritis (SpA) is an umbrella term which includes several inflammatory arthritides sharing common clinical features, such as sacroiliitis, spondylitis, peripheral arthritis/enthesitis and other extra-articular manifestations. Although typically presenting at a young age, SpA is often a relentlessly progressive disease even in this new era of biologics. In the last few years, much research has been generating on discovering new and more sensitive modalities in the use of magnetic resonance imaging (MRI) for assessing SpA. The advent of MRI has enabled clinicians to detect objective features of active inflammation, thereby allowing earlier diagnosis and more quantitative assessment of disease severity. Despite these rapid advancements, there have been few reports on examining the association between age and disease activity in SpA, especially with the use of these various new modalities of imaging. In this cross-sectional analysis, we examine the associations between age and the clinical and radiological disease activities in axial SpA using radiographs as well as different modalities of MRI. Methods: One hundred and twenty one patients fulfilling the Assessment of SpondyloArthritis International Society Classification Criteria for axial SpA were included in analyses. Patient demographics, disease activity and radiographic scores, as well as magnetic resonance imaging (MRI) with diffusion weighted imaging derived apparent diffusion coefficient values ((DWI(ADC)), were compared between patients older than and younger/equal to 40 years of age at a cross-sectional level. Variables with significant differences in univariate analyses were used as dependent variables in multivariate linear regression models adjusted for potential confounding/contributing factors. Results: Multivariate analysis showed that increasing age was significantly associated with higher Bath Ankylosing Spondylitis Functional Index (B=0.04, p<0.01) and Bath Ankylosing Spondylitis Metrology Index scores (B=0.03, p<0.01); as well as higher modified Stoke Ankylosing Spondylitis Spine Score (B=0.57, p<0.01). On MRI, increasing age was associated with a lower SpondyloArthritis Research Consortium of Canada MRI index (B=(-0.2), p=0.01) and DWI(ADC) (B=(-0.01), p<0.01) of the SI joints, but higher DWI(ADC) values of the axial spine (B=0.01, p=0.01). Conclusions: Increasing age in SpA was associated with greater functional impairment and structural damage, more inflammation of the axial spine, but less inflammation of the SI joints. Our findings are consistent with the traditional belief of SpA being an "ascending disease" and highlights the importance of different modalities of MRI in the diagnosis and disease monitoring of SpA. Disclosure of Interest: None declared